Synthesis of heterocylic compounds of biological interest from carbohydrate derivatives - Martinez Esperón, M.F. (2000)
The synthesis of some isoxazolic compounds from carbohydrate derivatives is described. These products are obtained by 1,3-dipolar cycloaddition reaction and their functionalization leads to derivatives with potential biological activities.